The magnitude of climate change in Natura 2000 areas in Slovenia - Ivajnšič, Danijel; Donša, Daša (Journal for Geography, 2018)
Europe has the world’s largest network of protected areas. Of course, climate change affects these areas no less than others. However, scientists reported that forecasts on maintaining climatic suitability for species of European concern in some Natura 2000 areas across Europe are even worse compared to surrounding unprotected areas. From the Slovenian perspective, the most climate change exposed Natura 2000 areas, according to current forecasts, can be found in the Sub-Mediterranean or Sub-Pannonia regions. More stable bioclimatic conditions, as expected, are estimated in the uplands. Such studies, which offer an objective assessment of the impact of climate change in the area, are of immense importance to managers and decision-makers in protected areas in order to prepare and potentially implement mitigation measures on the relevant vulnerable areas.